Pengaruh KIE Terhadap Sikap Ibu Nifas Tentang Vulva Hygiene Di Puskesmas Mayang - Widyastutik, Widyastutik; Widiatrilupi, Raden Maria Veronika (CV. ULIL ALBAB CORP, 2026)
Background: The postpartum period is a critical phase that is highly susceptible to infectious complications, particularly when vulva hygiene practices are not performed adequately. Postpartum mothers’ attitudes toward vulva hygiene play a crucial role in determining their adherence to recommended perineal care. Communication, Information, and Education (CIE) serve as systematic health promotion strategies aimed at influencing health behaviors through the delivery of accurate information and structured educational interventions. Methods:This study utilized a quasi-experimental design with a pretest–posttest control group approach involving 30 respondents, who were divided into an intervention group and a control group, each consisting of 15 participants. Data were collected using a validated attitude questionnaire comprising 25 Likert-scale statements. Data analysis was performed using paired t-tests and independent t-tests with a significance level of p < 0.05. Results: The intervention group demonstrated an increase in attitude scores by 22.6 points with a p-value of 0.000, whereas the control group showed an increase of only 4.8 points. A highly significant difference was observed between the two groups, with a p-value of 0.000. Conclusion: The structured Communication, Information, and Education intervention had a significant positive effect on improving postpartum mothers’ attitudes toward vulva hygiene at Puskesmas Mayang.